Empagliflozin suppresses mitochondrial reactive oxygen species generation and mitigates the inducibility of atrial fibrillation in diabetic rats - Koizumi, Takuya; Watanabe, Masaya; Yokota, Takashi; Tsuda, Masumi; Handa, Haruka; Koya, Jiro; Nishino, Kotaro; Tatsuta, Daishiro; Natsui, Hiroyuki; Kadosaka, Takahide; Koya, Taro; Nakao, Motoki; et al. (Frontiers in Cardiovascular Medicine, 2023)
Recent studies have demonstrated that sodium-glucose co-transporter-2 inhibitors (SGLT2-i) reduce the risk of atrial fibrillation (AF) in patients with diabetes mellitus (DM), in which oxidative stress due to increased reactive oxygen species (ROS) contributes to the pathogenesis of AF. We aimed to further investigate this, and examine whether the SGLT2-i empagliflozin suppresses mitochondrial-ROS generation and mitigates fibrosis. A high-fat diet and low-dose streptozotocin treatment were used to induce type-2 DM (T2DM) in Sprague-Dawley rats. The rats were randomly divided into three groups: control, DM, and DM treated with empagliflozin (30 mg/kg/day) for eight weeks. The mitochondrial respiratory capacity and ROS generation in the atrial myocardium were measured using a high-resolution respirometer. Oxidative stress markers and protein expression related to mitochondrial biogenesis and dynamics as well as the mitochondrial morphology were examined in the atrial tissue. Additionally, mitochondrial function was examined in H9c2 cardiomyoblasts. Atrial tachyarrhythmia (ATA) inducibility, interatrial conduction time (IACT), and fibrosis were also measured. Inducibility of ATA, fibrosis, and IACT were increased in rats with DM when compared to controls, all of which were restored by empagliflozin treatment. In addition, the rats with DM had increased mitochondrial-ROS with an impaired complex I-linked oxidative phosphorylation capacity. Importantly, empagliflozin seemed to ameliorate these impairments in mitochondrial function. Furthermore, empagliflozin reversed the decrease in phosphorylated AMPK expression and altered protein levels related to mitochondrial biogenesis and dynamics, and increased mitochondrial content. Empagliflozin also improved mitochondrial function in H9c2 cells cultured with high glucose medium. These data suggest that empagliflozin has a cardioprotective effect, at least in part, by reducing mitochondrial ROS generation through AMPK signalling pathways in the atrium of diabetic rats. This suggests that empagliflozin might suppress the development of AF in T2DM.